Comparison of Community Life in the Legend of Puyang Perahu Kawah and the Short Story Dua Wajah Ibu by Guntur Alam: A Sociological Analysis of Literature - Alvionita, Elica (Abjad Journal of Humanities & Education, 2024)
This study aims to compare the representation of life during the colonial and modern eras in literary works through a sociology of literature approach, focusing on the legend of "Puyang Perahu Kawah" and the short story "Dua Wajah Ibu." The legend of "Puyang Perahu Kawah," set during the Dutch colonial era, depicts the struggle of indigenous people against colonial oppression and their social and cultural values. In contrast, the short story "Dua Wajah Ibu" which depicts life in the city of Jakarta, highlights the challenges faced by rural migrants in adjusting to the urban environment. The research method used is qualitative descriptive, with reading and note-taking techniques to collect data from literary texts and related secondary sources. The results show that "Puyang Perahu Kawah" reflects social conflict and colonial oppression, while "Dua Wajah Ibu" reveals the social inequality and alienation experienced by migrants in big cities.